(untitled) (Journal of Fiber Bioengineering and Informatics, 2022)
Relevant research shows that pregnant women have a high sensitivity to electromagnetic radiation. At present, there is a lack of digital evaluation system for the simulation model of the degree of electromagnetic radiation exposure of pregnant women and the effectiveness of electromagnetic radiation shielding clothing for pregnant women. In this paper, the simulation model of pregnant woman and fetus is proposed, and the virtual fitting software is used to model the clothing, and finally the three-dimensional electromagnetic simulation software is used to combine the model and simulate the real situation. In this paper, the effects of electromagnetic radiation on pregnant women and fetuses before and after wearing electromagnetic radiation protective clothing were studied by means of digital evaluation. The results showed that the influence of electromagnetic radiation on pregnant women concentrated in the neck, chest, abdomen, leg; To a certain extent, electromagnetic radiation protective clothing can reduce the impact of radiation on pregnant women and fetuses. In this paper, a digital evaluation method is proposed, which provides a new idea for testing the effectiveness of electromagnetic shielding for pregnant women.